Casting techniques of cannonballs from the Akko 1 shipwreck: Archaeometallurgical investigation - Cvikel D.; Mentovich E.D.; Ashkenazi D.; Kahanov Y. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2013)
Eleven cannonballs were found in the Akko 1 shipwreck; two of them, a 9-pdr and a 24-pdr, were retrieved and studied using archaeometallurgical methods. Findings are reported in the present work. The aim of this research was to study the manufacturing technologies of the two cannonballs, and if possible to determine their date and manufacturing location according to the detailed technological analysis. The examination used optical microscopy, scanning electron microscopy, including energy dispersive spectroscopy, and hardness tests. The results show that the two cannonballs were casted by sand moulds, in two dissimilar processes and were made of different types of cast-iron. The non-uniformity of the 24-pdr cannonball could be the outcome of using a feeder of gray cast-iron in order to complete the casting process and compensating for the shrinkage of the metal. Based on their manufacturing process, it is suggested that the cannonballs were manufactured about the end of the first half of the nineteenth century. Combined with the archaeological and historical background, this supports the possibility that Akko 1 was a naval auxiliary vessel, which was in Akko harbour circa 1840.